2012
DOI: 10.1029/2012gl051037
|View full text |Cite
|
Sign up to set email alerts
|

Increase of global monsoon area and precipitation under global warming: A robust signal?

Abstract: [1] Monsoons, the most energetic tropical climate system, exert a great social and economic impact upon billions of people around the world. The global monsoon precipitation had an increasing trend over the past three decades. Whether or not this increasing trend will continue in the 21st century is investigated, based on simulations of three high-resolution atmospheric general circulation models that were forced by different future sea surface temperature (SST) warming patterns. The results show that the glob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 30 publications
15
99
0
1
Order By: Relevance
“…If this relationship remains valid under the altered atmospheric circulation patterns of an anthropogenically altered climate, then future monsoon responses may become stronger. This inference seems to be supported by recent instrumentally based observations (31) and model results (32,33).…”
supporting
confidence: 73%
“…If this relationship remains valid under the altered atmospheric circulation patterns of an anthropogenically altered climate, then future monsoon responses may become stronger. This inference seems to be supported by recent instrumentally based observations (31) and model results (32,33).…”
supporting
confidence: 73%
“…The 10-year analysis period is short, and this cautions against over-interpreting this apparent "tropical water sink". However it is of interest to note that a gradual strengthening of global monsoon rainfall extent and intensity has been observed, and is predicted to continue (Hsu et al, 2012). In any event, the difference between prior and posterior trends in Fig.…”
Section: Contributions To Sea Level Risementioning
confidence: 99%
“…Unfortunately, the change of the monsoons on global scale under increasing greenhouse gases forcing and aerosols has not been clearly documented. Recently, Hsu et al (2012) showed that most models in the CMIP3 and CMIP5 project an increase of global monsoon area and precipitation under global warming mainly attributable to the increases of moisture convergence and surface evaporation. However, evaluation of models' historical simulations and estimation of uncertainty in the corresponding future projections are prerequisite to assessment of the future changes.…”
Section: Introductionmentioning
confidence: 99%